Neurofilament light chain and S100B serum levels are associated with disease severity and outcome in patients with aneurysmal subarachnoid hemorrhage - Zhou, Zhangming; Zeng, Junyi; Yu, Shui; Zhao, Ying; Yang, Xiaoyi; Zhou, Yiren; Liang, Qingle (Frontiers in Neurology, 2022)
Objectives: Serum Neurofilament light chain (NfL) is a biomarker for neuroaxonal damage, and S100B is a blood marker for cerebral damage. The aim of the present study was to investigate the relationship between serum NfL and S100B levels, severity, and outcomes in patients with aneurysmal subarachnoid hemorrhage (aSAH). Methods: We prospectively recruited aSAH patients and healthy controls between January 2016 to January 2021. Clinical outcomes included mortality and poor outcome (modified Rankin scale score of 3-6) after 6 months. The ultrasensitive Simoa technique was used to evaluate NfL levels in the blood, and ELISA was used to detectS100B. Results: A total of 91 patients and 25 healthy controls were included in the study, with a death rate of 15.4%. The group of aSAH patients had significantly higher serum levels of NfL and S100B (P < 0.01). The levels of NfL and S100B increased when the Hunt-Hess, World Federation of Neurological Surgeons (WFNS), and Fisher grades increased (P < 0.01). Serum NfL and S100B levels were linked to a poor prognosis and low survival rates. The blood levels of NfL and S100B were found to be an independent predictor related with 6-month mortality in multivariable analysis. The areas under curves for NfL and S100B levels in serum were 0.959 and 0.912, respectively; the clinical diagnostic critical thresholds were 14.275 and 26.54 pg/mL, respectively; sensitivities were 0.947 and 0.921; and specificities were 0.849 and 0.811. Conclusions: The NfL and S100B value of aSAH patients within 12 days of admission were significantly associated with Hunt-Hess grade, WFNS and Fisher grade. The higher grade, the higher the NfL and S100B value, and poor prognosis. Serum NfL and S100B value could be considered as a feasible biomarker to predict the clinical prognosis of aSAH patients.